John Taylor, the Self-Made Poet, on Merit and Social Mobility in Mercantile London. Issue 2 (17th February 2017) - Finlayson, J. Caitlin
ABSTRACT: This paper explores John Taylor's fantasy of social advancement and meritocracy in his singular London Lord Mayor's Show, The Triumphs of Fame and Honour (1634). Taylor defines himself as a self-educated poet and working waterman, and his performance of this identity—the "Water Poet"—constitutes a significant part of his pageant book and heavily influences the themes of his pageant devices. The Triumphs of Fame and Honour presents a distinctive "working class" voice and is not merely an expression of the rampant commercialism typical of the Lord Mayor's Shows by writers such as Thomas Dekker. Instead, this mayoral show stresses mutability, which it links to temporal merit, to labour and to virtue in its reflection of a London of ordinary craftsmen, who may rise socially and economically by their labour and virtue. Taylor provides an alternative view of London life to that of the wealthy merchant class and the entrenched aristocracy, not revolutionary or subversive, but indicative of the emerging social mobility of the city, in which a waterman could become a popular, published poet and an apprentice the head of commercial London.